Assessing the validity of a linear inflation method in noninvasive blood pressure monitoring during the induction period of general anaesthesia. Issue 12 (December 2021) - Kikuchi, Ken-ichiro; Hirata, Naoyuki; Yoshikawa, Yusuke; Yamakage, Michiaki
Inflationary noninvasive blood pressure (iNIBP) monitoring can determine BP in a shorter time compared to conventional deflationary NIBP (dNIBP) monitoring. We assessed the efficacy of iNIBP monitoring during induction of general anaesthesia and tracheal intubation, which can cause rapid changes in haemodynamics. Our study included 14 surgery patients receiving tracheal intubation under general anaesthesia. Blood pressure was continuously measured using iNIBP monitoring. We recorded the percentage of successful iNIBP monitoring (measurements made without switching to dNIBP mode) during anaesthesia induction. We obtained 326 BP-measurements from 14 patients. The iNIPB mode was able to perform 90.9% of the measurements during the induction of general anaesthesia. iNIBP could determine BP even during periods of high blood pressure variability (31.6% [interquartile range; 22–40]). Our results validate the utility of iNIBP monitoring during the induction period of general anaesthesia, despite the rapid haemodynamic changes.